Unions, Training, and Firm Performance : Evidence from the British Workplace Employee Relations Survey - John T. Addison; Clive R. Belfield (Institute for the Study of Labor (IZA), 2004)
This paper uses a combination of workplace and matched-employee workplace data from the British 1998 Workplace Employee Relations Survey to examine the impact of unions and firm-provided training (incidence, intensity/coverage, and duration) on establishment performance. The performance effects of training are indexed not just by individual and median establishment earnings but also by subjective measures of plant labor productivity and financial performance. Union effects on training are fairly subtle, and somewhat more positive when using individual rather than plant-wide training data. A positive impact of training on earnings is also detected in both individual and plant-based wage data, although consistent with much recent research the effects of union recognition are at best muted. There are also some signs of a positive interaction term for unionism and training in the earnings equations, but by the same token negative effects are encountered when training duration is expressed in categorical terms and interacted with union recognition. Instrumenting training yielded positive results for labor productivity and the firm?s bottom line. While some negative effects of multiple unionism at the workplace now emerge, they seemingly do not operate through the training route.
Keywords: J33; J24; J51; 330; union recognition; bargaining structure; employer-provided training; training incidence; intensity/coverage and duration; earnings; Gewerkschaftlicher Organisationsgrad; Betriebliche Bildungsarbeit; Unternehmensentwicklung; Arbeitsproduktivität; Rentabilität; Arbeitsplatz; Schätzung; Grossbritannien